Changing One's View of Interior Design: an Educator's Perspective from the Pandemic. (16th February 2021) - Barron, Danielle L.
Abstract : Like most other educators, my world was rocked when my university was directed to transition to teaching fully online last March. The pandemic may have upended life as she knew it, but this educator found ways to keep her life, as well as those of her family and students, moving in the right direction.